Cloning and DNA sequence analysis of a Serpulina (Treponema) hyodysenteriae gene encoding a periplasmic flagellar sheath protein. - Koopman, M B (1992)
A Serpulina (Treponema) hyodysenteriae expression library was constructed in vector lambda ZAP and screened with a polyclonal antiserum raised against S. hyodysenteriae periplasmic flagella. A single immunoreactive plaque was chosen for further analysis. The recombinant phage from this plaque contained a gene encoding the 44-kDa protein that is on the outer layer (or sheath) of the periplasmic flagella. DNA sequence analysis showed that the gene encodes a protein of 320 amino acids. The protein is homologous to the flagellar sheath proteins of Treponema pallidum and Spirochaeta aurantia but not to any other flagellar proteins. We designated the cloned S. hyodysenteriae flagellar sheath protein gene flaA and the encoded protein FlaA. The 19 N-terminal amino acid residues of FlaA constitute a signal peptide that is cleaved from the protein before assembly onto the flagella in the periplasm. Amino acid residues 20 to 38 correspond to the N-terminal amino acid sequence of the native protein. Upstream from the gene, DNA motifs that are similar to the consensus Escherichia coli -35 and -10 promoter sequences and a ribosome binding site were identified. Downstream from the gene, two inverted repeat sequences that may serve as a rho-independent transcription termination signal are present.